English digits speech recognition system based on hidden Markov Models - Gunawan, Teddy Surya; Abushariah, Ahmad A. M.; Khalifa, Othman Omran (IIUM Press, 2011)
The field of Automatic Speech Recognition (ASR) is about 60 years old. There have been many interesting advances and developments since the invention of the first speech recognizer at Bell Labs in the early 1950' s. The development of ASR increased gradually until the invention of Hidden Markov Models (HMM) in early 1970's. Researchers' contribution were to make use of ASR technology to what can be seen nowadays of various advancements in fields like multi-modal, multi-linguaVcross-lingual ASR using statistical techniques such as HMM, SVM, neural network, etc [1].